Explanation of the attributes of believers in the light of Surah Al-Furqan - Dr. Maryam Raza; Asiya Batool (Journal of Religion and Society, 2025)
The holy Quran highlights numerous virtues of believers, showcasing the qualities Allah expects from those closest to Him. These virtues are mentioned both as ‘models of ideal behavior’ illustrating exemplary character traits and as ‘clear instructions’ aimed at refining human conduct. Their versatility spans ethical, economic, social, and worship-related dimensions, guiding believers toward comprehensive excellence.In the ‘final section of Surah Al-Furqan’ Allah outlines specific qualities that touch both individual and collective life, offering a roadmap for believers to attain proximity to Almighty Allah. These qualities encompass: Humility and modesty’ in worship and daily interaction. Steadfastness in truth’ and avoidance of falsehood. Compassion and generosity toward others, especially the needy Responsible stewardship’ of resources, reflecting ethical economic practices Integrity in social dealings, fostering trust and unity within the community. By embodying these traits, believers align themselves with divine expectations, ensuring both personal growth and societal harmony.